Power Measurement by Calorimetric Method Using Water Infrequency Range Between 1.7 Mhz To 3 Mhz - Shokrollahi, F; K. Lau, K; H. Tay, W; S. Lai, L (International Journal of Engineering and Technology, 2018)
Absorption is one of the most established processes for CO2 capturing. However, the current technologies used in this process suffer from several drawbacks. Meanwhile, the ultrasound technique is proposed as a new alternative technology to assist the CO2 absorption process due to both its physical and chemical effects. Yet, the chemical effect is still under developments. Between all the influencing parameters, the ultrasonic power and the frequency are the vital key parameters to investigate sonochemical effects during the CO2 Â Â Â absorption process. The aim of this paper is to measure the ultrasonic power of an ultrasonic vessel. The total electrical power measured by using the voltage and the flow. Simultaneously, the ultrasonic power determined by using the calorimetric method. The measurements were done by using water with different volumes and repeated for three different frequencies. The results showed that almost 51% of the electrical power converted into the ultrasonic power and were independent of liquid volume.Â Â